Developing Canva Learning Media Based on Problem-Based Learning to Improve Students' Problem-Solving Skills and Mathematics Learning Motivation - Lumban Toruan, Sischa Monika; Sitompul, Pardomuan; Asmin, Asmin (UIN Sunan Gunung Djati Bandung, 2025)
The purpose of this research is to develop Canva learning media based on Problem Based Learning to improve students' problem-solving abilities and mathematical learning motivation in valid, effective and practical mathematics learning. The method used in this research and development is the Four-D Model. Data can be used from validation questionnaires and student questionnaires. The results of the research show that Canva learning media is valid, practical and successful in improving students' problem-solving abilities and learning motivation. Students who learn from Canva learning media and LKPD show a sufficient increase in their problem-solving abilities and motivation to learn mathematics.